A Data-informed Model for Building Research Capacity in Out-of-home Care and Treatment Settings for Children and Youth. Issue 2 (3rd April 2022) - Portwood, Sharon G.; Boyd, A. Suzanne; Barber, Kenesha Smith
ABSTRACT: In response to the continuing need for agencies providing residential care and treatment to children and youth to develop and/or to enhance their ability to examine the effectiveness and efficiency of their services, this article explores successful strategies for building and sustaining research capacity in these settings. Between five and six years following a collaborative project to implement a program of outcomes research across 37 sites (representing 32 agencies) in two southeastern states, the authors investigated the extent to which research infrastructure and activities had been sustained and/or expanded since the project ended and examined the role of various factors in facilitating and supporting these efforts. At the time of this follow-up study, 24 (75%) of the agencies participating in the original study were still in operation (in the same or some modified form). Of these, 20 (83.3%) responded to an online survey. Overall, data supported a nine-step model for building research capacity that can serve as a guide for a wide range of agencies seeking to obtain scientifically sound data regarding the outcomes of children in their care.